Tera Ulang Peran Profetik Tuan Guru dalam Konteks Kebebasan Beragama di Pulau Lombok - Fawaizul Umam (Ulumuna, 2009)
Ulama (Islamic scholars) play important role in culturally paternalistic societies. Their prophetic role is theologically idealized as successors of prophets’ risâlah, mission. However, historically speaking, history yet often features reality that differs from their normative role. This paper aims to reevaluate the prophetic role of ulama in Lombok, called tuan guru, in the context of religious freedom praxsis. It is found that what is held by tuan guru in the realm of socio-politico-cultural tend to differ from his own existential theological spirit as one of socio-religious institutions. In the context of the praxis of religious freedom, tuan guru in general tend to play a role as a breeder and booster of anti pluralism discourses. Considering the theological claims of Islam itself as a spreader of mercy for all as well as political-cultural claims that Lombok is religious island, the island of thousand mosques, the realm seems ironic.